Information of Hadith Collection (my Hadith) - Norfidatul Ain (2013)
MY HADITH is a website that collected hadith sahih from kitab sahih bukhari and kitab sahih muslim , contents seven key components of home (website interface), hadith sahih bukhari, hadith sahih muslim, hadith 40, takhrij hadith, history of ulama' from kutubu sittah (imam bukhari, imam muslim, sunan ibn majah, sunan tirmizi, sunan abu daud, and sunan nasa'), and hadith gallery (content a picture kitab of hadith), the main language used in this website Arabic, This website is available in two languages ; English and Arabic languages.